Analysis of the Nature and Effects of Surety for Standing Property in Jurisprudence and Iranian Law - Ã˜Â§Ã™Â„Ã˜Â´Ã˜Â±Ã›ÂŒÃ™Â, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯Ã™Â…Ã™Â‡Ã˜Â¯Ã›ÂŒ; Ã™Â‚Ã˜Â§Ã˜Â³Ã™Â…Ã›ÂŒ, Ã˜Â±Ã˜Â¶Ã˜Â§ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Following jurisprudence, civil law has considered contract of surety (á¸amÄn) as conveyor of obligation and has limited surety to general properties or debts. Although this definition results in an incorrect surety of external objects, this very law has not abided by this conclusion in article 679 and along with most of jurists has passed a judgment on the correctness of responsibility surety (á¸amÄn-i uhda), which is a part of surety for pledged standing property (á¸amÄn-i aâyÄn-i maá¸mÅ«na). With the use of the proposition of uhda, which contrary to dhimma contains external objects, many of the contemporary jurists have considered the surety of standing property as an independent contract from surety of debts and with reliance on generalities have passed a judgment on the correctness of surety for standing property including both pledged and non-pledged as well as the correctness of insurance of the property that is in possession of its owner. On the basis of this analysis, the result of validation of external object on uhda is that the surety (guarantor) is first obliged to give back the property and in case of loss, will guarantee to give back a substitute to the owner. Given the generalities of law, such as article 10 of civil law, judgment on correctness of pledged standing property in statutory law is not encountered with a specific obstacle.